(3Gdcajd HeYGfj GdJfRjds - (3CHh GdMSjf Hf CHj HcQ Hf GdMSjf, YeGO GdOjf GdcfOj,J (B741 (3g` s
(3ChdgG (B:s
(3bhdg JYGdi (B: "(3EP JSJZjKhf QHce aGSJLGH dce(B" (3ef ShQI (B"(3GdCfaGd(B" s
(3BNQgG (B:s
(3JaSjQ bhdg JYGdi(B: "(3hdGJUd Ydi CMO efge eGJ CHOkG (B" (3ef ShQI (B"(3GdJhHI(B" s
(3GdfSNI HgG MhGTs
(3cJHJ aj MjGI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B316s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B39 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1502s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs